Evaluation of Peripheral Lymphadenopathies in Children in a Single Center: Predictive Factors for Malignancy - Işık, Pamir; Belen Apak, Fatma Burcu; Demir, Tuğba Acer (Klinische Pädiatrie, 2024)
Background Lymphadenopathy (LAP) is a common finding in pediatric patients. It was aimed to determine predictive factors in distinguishing cases with malignant or benign lymphadenopathy in this study.Subjects and methods Between January 2022 and January 2023, 101 patients (1-16 years old) with lymphadenopathy were retrospectively examined.Results LAP was localized in 80.2% (n=81) cases and generalized in 19.8% (n=20) cases. In 60 cases (59.4%), lymph node sizes were found to be greater than 20×20 mm in width and length. The most common infectious causative agent was Epstein Barr Virus (EBV). Seven (6.9%) patients underwent biopsy and all were diagnosed with malignancy. When the benign and malignant groups were compared, age, lymph node length, and width on physical examination, anteroposterior and longitudinal diameter of the lymph node on ultrasonography (USG) were statistically significantly higher in the malignant group (p<0.05). The presence of supraclavicular lymphadenopathy was found to be an important factor in differentiating the malignant group (p<0.003). The most important factors in distinguishing the groups are respectively were the anteroposterior diameter of the lymph node on ultrasonography and the presence supraclavicular lymph node in multivariate logistic regression analysis.Conclusion It is not always easy to distinguish benign and malignant etiologies in patients with lymphadenopathy. A detailed history, a careful physical examination, laboratory studies, and excisional biopsy are guiding.
Keywords: Peripheral lymphadenopathy; Malignancy; Infection; Children